The access and welfare impacts of telecommunications technology in Peru - Maximo Torero (University of Bonn, Center for Development Research (ZEF), 2000)
This paper attempts to assess three main issues on Peruvian telecommunications technology: what are the main variables that explain the demand for access to telephone services; how important is access to telephone services in explaining the transition out of poverty, and what are the consumption and welfare impacts of the significant increase in the supply of telephone lines since the divestiture in 1994 of the Peruvian telephone services. To accomplish our goal we will use two methodologies. Firstly, we will concentrate on residential telephony based on a countrywide representative consumer expenditure survey (The World Bank's Living Standards Measurement Survey). With this household survey the demand for access to telephone services was modeled and the effects of access to a telephone on poverty was analyzed. The main result showed that access to a telephone is important in explaining why low income households do not drop into poverty, but that it is not significant in explaining the transition between poor and non-poor status. Additionally, the presence of these surveys for 1985, 91, 94 and 1997, allowed us to estimate the welfare impacts at different socioeconomic levels of the various institutional changes in telephone services before and after privatization. The second methodology takes advantage of a panel of households for Metropolitan Lima allowing us to estimate partial demand equations of access to telephone services in order to evaluate consumers' welfare pre and post divestiture showing the presence of an important positive consumer surplus of access to a residential telephone. Both methodologies measured how welfare gains coming from more people having access to telephone lines might have compensated for higher usage rates as the result of privatization. The main objective of these methodologies is therefore to assess which types of households, classified according to their observable characteristics, bear a greater portion of the burden or enjoy most of the benefits of the changes brought about by privatization. – – Die vorliegende Studie beschäftigt sich mit drei Problemen, die im Zusammenhang mit Veränderungen auf dem Gebiet der peruanischen Telekommunikationsdienste stehen. Diese Probleme sind: erstens die Frage nach den wichtigsten Variablen, die die Nachfrage nach Telefondiensten bestimmen; zweitens, die Rolle des Zugangs zu Telekommunikationsdiensten in Abhängigkeit verschiedener Stadien materieller Armut; drittens stellt sich die Frage, inwieweit sich die – seit der Teilprivatisierung des Telekommunikationsmarktes im Jahre 1994 andauernde – stetige steigende Anzahl an Telefonanschlüssen auf Konsum- und Wohlfahrtskriterien auswirkt. Zur Untersuchung dieser Fragen werden zwei verschiedene Methoden angewendet. Zum einen werden Daten herangezogen, die im Rahmen einer repräsentativen und landesweiten Konsumentenbefragung erhoben wurden. Diese Daten erlauben auf der Haushaltsebene eine Modellierung der Nachfrage nach Telekommunikationsdiensten sowie des potentiellen Einflusses der Telefonnutzung auf materielle Armut. Die Ergebnisse zeigen, dass der Zugang zu Telefonen, insbesondere für Haushalte mit niedrigem Einkommen, wichtig ist, um ihren ökonomischen Status zu erhalten bzw. zu verbessern. Andererseits ergab sich aber kein signifikanter Zusammenhang zwischen der Nutzung der Dienste und der Überwindung von Armut. Datensätze aus den Jahren 1985, 1991, 1994 sowie 1997 wurden genutzt, um die Wohlfahrtseffekte, die die institutionellen Veränderungen auf dem Telekommunikationssektor mit sich brachten, auf verschiedenen sozioökonomischen Niveaus für den Zeitraum vor bzw. nach der Privatisierung des Sektors zu untersuchen. Schließlich konnten mit Hilfe von Erhebungen in Lima partielle Nachfragefunktionen vom Zugang zu Telekommunikationsdiensten vor und nach der Privatisierung geschätzt werden. Die so gewonnenen Erkenntnisse bezüglich der Konsumentenrenten lassen den Schluss zu, dass insbesondere die Nutzer von privaten Hausanschlüssen von den Veränderungen profitieren.
Keywords: 330; Telekommunikation; Telefonnetz; Mediennutzung; Armut; Privatisierung; Wohlfahrtsanalyse; Peru